A hydrolysis-resistant PC resin composition and preparation method thereof

By blending hydrophobic PP or PE with PC and adding polypropylene-co-oxazoline random copolymer and aluminum trioxide as compatibilizers and hydrolysis stabilizers, a hydrolysis-resistant PC resin composition is formed, which solves the problem of hydrolysis of PC materials in high temperature and high humidity environments, and achieves high hydrolysis resistance and good mechanical properties of the material.

CN115850935BActive Publication Date: 2025-03-14SHANGHAI KUMHOSUNNY JINSHAN PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211481413.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-03-14
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

Existing PC materials are easily hydrolyzed in high temperature and high humidity environments, resulting in a decrease in impact toughness, elongation of breakage and surface gloss of the material, which cannot meet the needs of long-term use.

Method used

A hydrophobic PP or PE is blended with PC and added with polypropylene-co-oxazoline random copolymer as a compatibilizer and aluminum trioxide as a hydrolysis stabilizer, a hydrolysis resistant PC resin composition is formed.

Benefits of technology

After aging at 85°C and 85% humidity for 1000 hours, the impact, elongation of breakage and gloss retention rates reached more than 95%, which significantly improved the hydrolysis resistance of the PC material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003961792940000021
    Figure BDA0003961792940000021
Patent Text Reader

Abstract

The present invention provides a hydrolysis-resistant PC resin composition and a preparation method thereof; the composition comprises the following components in parts by weight: PC resin: 83-93 parts; hydrophobic resin: 4-9 parts; compatibilizer: 3-8 parts; hydrolysis stabilizer: 0.2-2 parts; toughening agent: 0.5-3 parts; antioxidant: 0.1-0.5 parts; the preparation method of the composition comprises the following steps: (1) preparing the components according to the above parts by weight; (2) adding the above weight percentages to a high-speed mixer, mixing them thoroughly, and then placing them in a screw machine for melt extrusion, cooling and granulation to obtain a hydrolysis-resistant PC resin composition. Compared with the prior art, the PC resin composition obtained by the present invention has excellent toughness, heat resistance and rigidity. At the same time, the resin composition has excellent hydrolysis resistance, and the resin composition is simple to prepare, has low material cost and high production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a hydrolysis-resistant PC resin composition and a preparation method thereof. Background Art

[0002] Bisphenol A polycarbonate PC is a material with excellent comprehensive performance. Its outstanding transparency, high toughness and high heat resistance make it widely used in various industries. PC polymer chain is easily hydrolyzed due to ester bonds, especially in high temperature and high humidity environment, PC will be severely degraded, resulting in a significant decrease in the impact toughness and elongation at break of the material, and a significant decrease in surface gloss. This reaction will be accelerated in an overly acidic or alkaline environment. Therefore, PC is often not used directly in a long-term high temperature and high humidity environment.

[0003] The current method to improve the hydrolysis resistance of PC is to mix PC with other resins, such as PC / ABS alloy. The essence of this method is to mix hydrolysis-resistant ABS with PC, but it does not completely change the defect of PC's lack of hydrolysis resistance. Therefore, the improvement is limited, and the addition of ABS will greatly reduce the heat resistance of PC.

[0004] Another method to improve the hydrolysis resistance of PC is to add a capping agent to react with the terminal carboxyl group of PC, thereby improving the hydrolysis resistance of PC. Such as epoxy grafting, maleic anhydride grafting, and oxazoline copolymer. However, the reactivity of these capping agents is too strong, which will destroy the pH of the system, so they cannot effectively improve the hydrolysis resistance of PC, and sometimes even cause PC to degrade faster.

[0005] The use of hydrolysis resistance modifiers such as polycarbodiimide is an effective way to improve polyester products. It mainly reacts with the carboxylic acid end groups generated by polymer hydrolysis to generate stable ureides, thereby improving hydrolysis stability. However, it has a certain alkalinity, which will cause significant degradation of PC materials during high-temperature extrusion processing. Therefore, polycarbodiimide cannot improve the hydrolysis resistance of PC.

[0006] Patent CN114133724 discloses a hydrolysis-resistant PC / TPU composite material, the method comprising the following steps:

[0007] (1) reacting a carbodiimide modified isocyanate mixture with a polycarbonate polyol in the presence of an amine chain extender to prepare a modified polyurethane reaction liquid; (2) reacting phosgene with an excess of bisphenol A to polymerize to generate a terminal hydroxyl polycarbonate; adding diisocyanate to react with the terminal hydroxyl polycarbonate to generate a modified polycarbonate, and preparing a powder; (3) mixing the powdered modified polycarbonate with the modified polyurethane reaction liquid, melt-extruding, and granulating to obtain the polycarbonate composite material. The obtained composite material has excellent hydrolysis resistance. After aging at high temperature and high humidity for 600 hours, the impact resistance of the material reaches 96-98%. Although the wet heat aging performance retention rate of the material is very good, the basic mechanical properties of this PC / TPU are far behind those of PC.

[0008] Patent CN109021534 discloses a high temperature and high humidity resistant polycarbonate composition, which comprises 65-95 parts of polycarbonate, 0-20 parts of reinforcing component, 2-6 parts of flame retardant, 0.2-0.5 parts of anti-dripping agent, 2-5 parts of organosilicon toughening agent, 0.2-1 parts of oxazoline chain extender, and 0.1-2.5 parts of other additives. The prepared polycarbonate has excellent high temperature and high humidity resistance and has a very high performance retention rate after 1000 hours of "double 85" (85% humidity, 85°C) wet heat aging. The impact retention rate can reach 45-81%, but the retention rate of elongation at break is very low, only 3-51%, which cannot meet the requirements for some occasions with high toughness requirements.

[0009] So far, there is no PC material modified by blending, whose impact retention, elongation at break and surface gloss retention can reach more than 95% after 1000h of double 85 wet heat aging test. Summary of the invention

[0010] In view of the defects in the prior art, the present invention provides a hydrolysis-resistant PC resin composition and a preparation method thereof.

[0011] The objective of the present invention is achieved through the following technical solutions:

[0012] The present invention provides a hydrolysis-resistant PC resin composition, comprising the following components in parts by weight:

[0013]

[0014] Preferably, the PC resin is a bisphenol A type polycarbonate resin. The bisphenol A type polycarbonate resin is preferably a PC resin with a melt index of 2-10 g / 10 min (test conditions 300 degrees, 1.2 kg). The impact performance of the resin used is more stable.

[0015] Preferably, the hydrophobic resin includes polypropylene resin PP and / or polyethylene resin PE. Due to the incompatibility between hydrophobic PP or PE and hydrophilic resin PC, during the molding process, PP and PE tend to migrate to the surface of PC, forming a hydrophobic barrier layer on the surface of PC, making it difficult for water to attack PC, thereby improving the hydrolysis resistance of PC to a certain extent.

[0016] Preferably, the compatibilizer is a polypropylene-co-oxazoline random copolymer, and the amount of oxazoline groups is 1.2 to 1.8 mmol / g. The oxazoline group reacts with the terminal carboxyl group of PC, as shown in the following formula, to form a polypropylene-co-polycarbonate copolymer, one end of the reaction product reacts with PC, and the other end has very good compatibility with PP, which can effectively improve the compatibility of PC with PP or PE. Improving compatibility can improve the mechanical properties of PC / PP materials, but it cannot be improved too much, and it is also necessary to ensure that PP and / or PE resins migrate outward. The compatibilizer of the present invention can well control this result.

[0017] Preferably, the hydrolysis stabilizer comprises aluminum oxide, the particle size is less than 50 microns, and the purity of aluminum oxide is greater than 72%. The small particle size ensures the maintenance of the toughness of PC, and the high purity of aluminum oxide is to ensure low impurity content and reduce the impact of impurities on PC degradation. Aluminum oxide acts on the acidic group (carboxyl) and basic group (oxazoline) in the system respectively, and does not over-react with acid or base, thereby stabilizing the pH of the system and preventing the hydrolysis reaction of PC.

[0018] Preferably, the toughening agent comprises MBS rubber powder of core-shell structure, wherein the core is butadiene rubber, the shell is MMA, and the particle size is 150-210 nm. In this case, the toughening efficiency is the highest.

[0019] Preferably, the antioxidant is one of phenolic antioxidants and phosphite antioxidants or a mixture of the two. The phenolic antioxidant is Irganox 1076; the phosphite antioxidant is Irgafos 168.

[0020] The present invention provides a method for preparing a hydrolysis-resistant PC resin composition, which specifically comprises the following steps:

[0021] (1) Prepare the following components by weight:

[0022]

[0023] (2) The components in step (1) are weighed according to the above weight proportions and fully mixed, and then placed in a screw machine for melt extrusion, cooling and granulation to obtain a hydrolysis-resistant PC resin composition.

[0024] Preferably, the extrusion temperature in step (2) is 290-340° C., preferably 300-330° C., to ensure that the oxazoline group reacts fully with PC. The screw speed is 200-500 rpm. The mixing is carried out in a high-speed mixer.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention utilizes the incompatibility between hydrophobic PP or PE and hydrophilic resin PC. During the molding process, PP and PE tend to migrate to the surface of PC, forming a hydrophobic barrier layer on the surface of PC, making it difficult for water to attack PC, thereby improving the hydrolysis resistance of PC to a certain extent.

[0027] 2. The present invention uses polypropylene-co-oxazoline random copolymer as a compatibilizer for PC and PP or PE. The oxazoline group reacts with the terminal carboxyl group of PC to form a polypropylene-co-polycarbonate copolymer (as shown in the following reaction formula). This reaction product can effectively improve the compatibility of PC with PP or PE.

[0028]

[0029] 3. In order to further improve the hydrolysis resistance of PC, the present invention adds amphiphilic aluminum oxide to PC. Aluminum oxide reacts with the acidic group (carboxyl) and the basic group (oxazoline) in the system respectively, and does not over-react with acid or base, thereby stabilizing the pH of the system and preventing the hydrolysis reaction of PC. Selecting aluminum oxide with a purity of more than 72% as the anti-hydrolysis agent can reduce the catalytic degradation of PC by impurity metals in aluminum oxide.

[0030] 4. In order to further promote the reaction between PC and oxazoline groups, the present invention effectively promotes the reaction by increasing the extrusion temperature to above 280° C., so that the obtained PC / PP alloy has excellent compatibility.

[0031] 5. The present invention ensures that the mechanical properties of the PC resin composition are equivalent to those of pure PC by selecting the appropriate size of the toughening agent MBS and the appropriate amount of PP added.

[0032] 6. The PC resin composition obtained by the present invention has excellent toughness, heat resistance and rigidity. At the same time, the resin composition has excellent hydrolysis resistance. After aging for 1000 hours at 85 degrees Celsius and 85% humidity, the impact, elongation at break and gloss retention of the material reach more than 95%. In addition, the resin composition is easy to prepare, has low material cost and high production efficiency. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0034] The materials in Table 1 and Table 2 are as follows:

[0035] PC1: PC1100, melt index 10g / 10min, Lotte, South Korea;

[0036] PC2: PC3030PJ, melt index 2-3g / 10min, Samyang, Korea;

[0037] PP: K7926, SECCO;

[0038] PE: LL0209AA, SECCO;

[0039] Compatibilizer: IX-4-RP-7, oxazoline group content is 1.35mmol / g, Japan Catalyst;

[0040] Hydrolysis stabilizer 1: Catapal D, purity 76%, particle size 40 μm, Sasol;

[0041] Hydrolysis stabilizer 2: Pural 200, purity 80%, particle size 40 μm, Sasol;

[0042] Hydrolysis stabilizer 3: Pupal BT, purity 64%, particle size 5-10 μm, Sasol;

[0043] MBS1: BTA-717, refractive index = 1.54, particle size 150-200 nm, Rohm & Haas;

[0044] MBS2: EXL 2678, refractive index = 1.54, particle size 250nm, Rohm&Haas;

[0045] Antioxidant 1: Irganox 1076, phenolic antioxidant, BASF;

[0046] Antioxidant 2: Irgafos 168, phosphite antioxidant, BASF;

[0047] Performance evaluation methods and implementation standards:

[0048] Tensile elongation at break: tested according to ISO527:2012(E) standard, tensile rate 50mm / min, test temperature 23℃;

[0049] Charpy notched impact strength: tested according to ISO 179-1:2010(E) standard, with an impact energy of 4J and a test temperature of 23°C;

[0050] Vicat softening point: tested according to ISO 306:2013(E) standard, test conditions are 5Kg, 50℃ / h;

[0051] Flexural modulus: tested according to ISO 178:2010(E) standard, test speed is 2mm / min;

[0052] Glossiness: Test the glossiness of the smooth panel (molded with a polishing degree of 10000#) according to ASTM D523:2008 standard, and test the glossiness at an angle of 20°;

[0053] Test hydrolysis resistance: The specimens were aged for 1000 hours in an environment of 85 degrees Celsius and 85% humidity, and the impact and tensile fracture growth rates were tested.

[0054] Embodiment 1~5:

[0055] A method for preparing a hydrolysis-resistant PC resin composition, the method comprising the following steps:

[0056] According to the weight percentage of the ingredients in Table 1, the raw materials were added into a high-speed mixer and mixed thoroughly, and then placed in a screw machine for melt extrusion at an extrusion temperature of 290 to 310° C. and a screw speed of 500 rpm, and cooled and granulated to obtain the product.

[0057] Table 1 Example formula weight parts and properties

[0058]

[0059]

[0060] Comparative Examples 1 to 6:

[0061] According to the weight percentage of the ingredients in Table 2, the raw materials were added to a high-speed mixer and mixed thoroughly, and then placed in a screw machine for melt extrusion at an extrusion temperature of 290 to 310° C. (Comparative Examples 2 to 6) and a screw speed of 500 rpm, and cooled and granulated to obtain the product.

[0062] The extrusion temperature of Comparative Example 1 is 230-260°C.

[0063] Table 2 Comparative Example Formula Weight Parts

[0064]

[0065]

[0066] Comparative Example 1: Compared with Example 1, the extrusion temperature was lowered, and the reaction between PC and the compatibilizer was insufficient. Due to the compatibility problem, the performance was very poor.

[0067] Comparative Example 2, compared with Example 1, PP was removed, there was no surface moisture isolation layer, and the material was severely hydrolyzed;

[0068] Comparative Example 3, compared with Example 1, the hydrolysis stabilizer was removed, and the performance before aging was good, but after aging, the performance deteriorated seriously;

[0069] Comparative Example 4, compared with Example 1, the hydrolysis stabilizer was replaced with low-purity aluminum oxide. Due to the degradation of PC caused by impurities, the performance was poor;

[0070] Comparative Example 5 shows the performance of pure PC, and it can be seen that its hydrolysis resistance is poor.

[0071] In Comparative Example 6, compared with Example 1, the compatibilizer was removed. Due to poor compatibility, the material as a whole exhibited poor mechanical properties and performance retention.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A hydrolysis-resistant PC resin composition, characterized in that: The composition comprises the following components in parts by weight: The hydrophobic resin includes polypropylene resin PP and / or polyethylene resin PE; The compatibilizer is a polypropylene-co-oxazoline random copolymer, and the amount of oxazoline groups is 1.2 to 1.8 mmol / g; The hydrolysis stabilizer is aluminum oxide with a particle size of less than 50 microns; the purity of aluminum oxide is greater than 72%; The extrusion temperature when preparing the hydrolysis-resistant PC resin composition is 290-340°C.

2. The hydrolysis-resistant PC resin composition according to claim 1, characterized in that: The PC resin includes bisphenol A type polycarbonate resin.

3. The hydrolysis-resistant PC resin composition according to claim 1, characterized in that: The antioxidant is one or a mixture of phenolic and phosphite antioxidants.

4. A method for preparing a hydrolysis-resistant PC resin composition according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Prepare the following components by weight: (2) The components in step (1) are mixed according to the above weight proportions, and after being fully mixed, melt-extruded, cooled and granulated to obtain a hydrolysis-resistant PC resin composition.

5. The method for preparing a hydrolysis-resistant PC resin composition according to claim 4, characterized in that: In step (2), the screw speed is 200-500 rpm.

Citation Information

Patent Citations

  • High-toughness transparent PC / PP resin composition as well as preparation method and application thereof

    CN114350134A

  • Hydrolysis-resistant polycarbonate composition

    WO2022043424A1